Weight reduction practices and injury frequency in Belgian judo players - Ramon, K.; Zinzen, E.; van Malderen, C.; Deriemaeker, P.; Clarys, P. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Introduction Judo is a contact sport with heavy demands for the athletes. Due to the nature of the sport and the training intensity it is a sport with a rather high injury rate. As competition is performed in weight classes a number of athletes are involved in weight reduction practices. The aim of our study was to collect information on the weight reduction practices and the frequency and types of injuries in Belgian judo competitors. Methods All judo competitors of a Belgian tournament (Trofee van Vlaanderen/ Flanders Trophy) were asked to complete a questionnaire. The judokas were asked if they were involved in weight reduction practices and how they achieve their competition weight. If they are using a weight reduction method, it was asked who decided to participate in the weight control method and which method was used. If injuries occurred during the last year further questions were asked to know the type of injury and the duration of inactivity due the reported injury. Results 515 judo competitors completed the questionnaire. 357 males in different age categories participated to the study : 183 age 13 -14, 103 age 15-16, 28 age 17-19 and 43 age > 20 and 158 females in the respective age categories 75 age 13-14, 48 age 15-16, 24 age 17-19 and 11 age > 20. The number of judokas performing weight reduction was comparable for males and females (respectively 39,5% and 36,7%). 79,3% of the males and 67,3% of the females reported that the decision to perform weight reduction was a personal one while the remaining 39,8% performed weight reduction after advice of another person. Only 20,7% of the males and 32,7% of the females received advise concerning the weight reduction method. The most used practices were: diet (64,9% for the males; 54,7% for the females); additional training (31,5% for the males; 35,9% for the females); and dehydration (4,5% and 9,4% respectively for males and females). The reported injury rates were equally comparable between males and females: respectively 32,7% for the boys and 20,7% for the girls. The most frequently reported injuries were knee (33%); shoulder (18%), foot (14%), elbow (10%), hands (8%) and back (7%). The period of inactivity varied between (1 week and 12 months), with an average of 65 days. Discussion Due to the low ranking of the competition and due to the small number of participants in some categories results should be interpreted with uttermost precaution. The number of judokas involved in weight reduction is striking. The used methods are often inappropriate and do not permit optimal performance during training and competition. The high incidence of injuries at some specific locations may be an indication for more prevention oriented training such as strengthening of the shoulders, knees and elbows.